2005
DOI: 10.1111/j.1399-0004.2004.00405.x
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial comparing alternative approaches to prenatal diagnosis counseling in advanced maternal age patients

Abstract: Prenatal diagnosis (PND) is offered routinely as part of pregnancy care to a large number of women at increased risk of fetal anomalies. Despite an extraordinary growth in the use of PND and significant resource allocation, few studies have examined outcomes of PND counseling, and virtually no research has evaluated the relative efficacy of various approaches to genetic counseling. This study was a randomized trial that compared which counseling methods - individual, group, and use of a decision aid - are effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
137
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(142 citation statements)
references
References 39 publications
5
137
0
Order By: Relevance
“…[12][13][14]21 Other studies evaluating the effect of patient decision aids on decisionmaking regarding prenatal testing for fetal chromosomal abnormalities have been published. Previous studies have reported on the application of booklets with worksheets, 22,23 information films, 24,25 and interactive computer programmes. [26][27][28] Although results from these studies cannot easily be compared because of heterogeneity in settings, interventions and outcome measures, most have general findings that correspond with the results of the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14]21 Other studies evaluating the effect of patient decision aids on decisionmaking regarding prenatal testing for fetal chromosomal abnormalities have been published. Previous studies have reported on the application of booklets with worksheets, 22,23 information films, 24,25 and interactive computer programmes. [26][27][28] Although results from these studies cannot easily be compared because of heterogeneity in settings, interventions and outcome measures, most have general findings that correspond with the results of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28] Although results from these studies cannot easily be compared because of heterogeneity in settings, interventions and outcome measures, most have general findings that correspond with the results of the present study. Nearly all found the application of a decision aid to increase pregnant women's decision-relevant knowledge [22][23][24][25][26][27] and informed decision-making. 23,25 In this trial, high baseline levels of informed decision-making in the control group notwithstanding the application of the web-based multimedia decision aid resulted in an increase in informed decision-making that was slightly higher than the effect found in previous evaluations.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with the results of a randomized trial comparing different prenatal counselling methods, which showed that women and their partners preferred individual genetic counselling, while learned best in group counselling sessions. 13 Therefore, none of the two approaches has proven superior to the other one in relation to the parameters analysed; in addition, both approaches have been suggested to be similarly effective in identifying risk factors beyond AMA in a previous study, 12 thus leading to the conclusion that either one can be adopted.…”
Section: Involvement Of Partner and Other Family Membersmentioning
confidence: 99%
“…Nevertheless, evidence on the outcomes, as well as on the optimal approach of genetic counselling preceding IPP is extremely scarce. 13 In recent years, at the Academic Hospital Policlinico S.OrsolaMalpighi, women of AMA undergoing IPP at the Unit of Obstetrics, have been receiving pre-test genetic counselling from the staff of the Medical Genetics Unit. Counselling approach has changed over time because of organization reasons: at first (from January 2010 to June 2011), women/couples used to undergo individual counselling sessions, whereas since July 2011, counselling has been offered in the form of group sessions.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13] Use of decision aids for prenatal counseling using structured, paper-based or basic electronic tools has been associated with less decision conflict, improved knowledge, and in some cases, increased uptake of prenatal testing. [14][15][16][17][18] Such tools can facilitate an improved informed consent process, yet few decision aids have been developed and evaluated in the United States, particularly for use in low literacy populations. 11 In 2009, Kuppermann et al showed that use of an interactive prenatal diagnostic decision tool resulted in better patient satisfaction, more decision certainty, and more accurate estimates of risk among women receiving prenatal genetic counseling.…”
Section: Introductionmentioning
confidence: 99%